2020
DOI: 10.20944/preprints202011.0276.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Vitamin D Modulates Intestinal Microbiota in Inflammatory Bowel Diseases

Abstract: Inflammatory bowel disease (IBD) is a chronic disease in the gastrointestinal tract (GIT). IBD include ulcerative colitis (UC), which generally affects only the large intestine mucosa and submucosa, and Crohn’s disease (CD), which may affect any part of the GIT by transmural inflammation. Both UC and CD are associated with an imbalance of the gut microbiota composition and injuries in the intestinal mucosa. The intestinal dysbiosis is related to a reduction in butyrate-producing species, impairing th… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 143 publications
(174 reference statements)
0
14
0
Order By: Relevance
“…Consequently, many of the effects of vitamin D on immune, mitochondria, epigenetic, and melatonergic pathway regulation may be mediated via effects in the gut. The prevention of gut permeability by vitamin D [ 53 ], may therefore be mediated via the upregulation of butyrate, whilst butyrate also acts to upregulate vitamin D receptor signaling [ 54 ]. Vitamin D may also suppress pro-inflammatory cytokine production [ 55 ], indicating that it may decrease pro-inflammatory cytokine-induced IDO, thereby impacting on the kynurenine/tryptophan ratio and inflammation driven AhR activation.…”
Section: Vitamin D and Covid-19mentioning
confidence: 99%
“…Consequently, many of the effects of vitamin D on immune, mitochondria, epigenetic, and melatonergic pathway regulation may be mediated via effects in the gut. The prevention of gut permeability by vitamin D [ 53 ], may therefore be mediated via the upregulation of butyrate, whilst butyrate also acts to upregulate vitamin D receptor signaling [ 54 ]. Vitamin D may also suppress pro-inflammatory cytokine production [ 55 ], indicating that it may decrease pro-inflammatory cytokine-induced IDO, thereby impacting on the kynurenine/tryptophan ratio and inflammation driven AhR activation.…”
Section: Vitamin D and Covid-19mentioning
confidence: 99%
“…The goblet cells are scattered between the intestinal epithelial cells and resemble a high foot goblet, and their number gradually increases from the small to the large intestine, consistent with changes in intestinal bacteria (Battistini et al, 2020). The mucins secreted by goblet cells combine with extracellular water and inorganic salts to form a mucus layer, which interacts with intestinal epithelial cells, intestinal microecology, and the host's immune system to jointly maintain the homeostasis of the intestinal internal environment (Birchenough et al, 2015).…”
Section: Discussionmentioning
confidence: 84%
“…Vitamin D suppresses pro‐inflammatory responses 32 and enhances intestinal barrier integrity through regulation of the vitamin D receptor (VDR): VDR has been identified as the first human gene to shape the gut microbiome 33 . The gut dysbiosis‐associated inflammatory diseases, such as IBD and MS, are also strongly associated with vitamin D levels 34,35 Moreover, Lactobacillus was decreased in VDR depletion or failure of active vitamin D production 36 . A previous study also reported that the shift in gut microbiome after NBUVB exposure was associated with increased vitamin D levels 8 .…”
Section: Discussionmentioning
confidence: 99%